Medical nutritional therapy in chronic pancreatitis - Freesia Novita Kusumawardani; Diyah Eka Andayani (World Nutrition Journal, 2022)
Chronic pancreatitis is a complex disease associated with significant morbidity and mortality. Patients with chronic pancreatitis are at risk for malnutrition and nutrient deficiency caused primarily by malabsorption, inadequate intake, and inflammation. Poor nutritional status may negatively affect disease’s outcome. Medical nutritional therapy which include screening and assessment of malnutrition followed by optimal nutritional intervention for patient at risk should be the cornerstone of chronic pancreatitis multidisciplinary treatment.